Perception of academic background and learning motivation of students in higher education: Analysis in the context of english language learning - Permata, Divia Atma (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the relationship between students' perceptions of their academic background and their motivation to learn in higher education, particularly in the context of learning English as a foreign language. Many studies have found that academic background is often assumed to be a predictor of academic success at the advanced level. However, empirical findings indicate that psychological factors such as self-perception, intrinsic motivation, and learning environment factors play an equally significant role. This article applies a study of the dynamics of this relationship by highlighting the differences between students with linear and non-linear academic backgrounds, and applying theories of motivation and self-efficacy. The results indicate that positive perceptions of academic readiness tend to strengthen learning motivation, although the correlation is not always strongly significant. The implications of this research emphasize the importance of pedagogical interventions, strengthening self-regulation, and academic support for students with different backgrounds.